The consequences of social category faultlines in high- and low-context cultures: A comparative study of Brazil and Germany - Burmann, Kathrin; Semrau, Thorsten (Frontiers in Psychology, 2022)
The present study sheds light on how differences between high- and low-context cultures influence the consequences of social category faultlines. To develop our theoretical arguments, we integrate ideas from faultline theory and Hall’s theory on cultural contexts. We test our hypotheses using survey data from 54 teams in the banking industry in Germany, a nation with a low-context culture, and in Brazil, a country with a high-context culture. In line with our theorizing, the study results reveal that whether social category faultline strength stimulates task conflict and is thus detrimental to team performance depends on the societal culture in which teams operate. Specifically, we observe that social category faultlines stimulate task conflict and thus have a negative indirect effect on team performance in Germany’s low-context culture, while we find no such effects in the high-context culture of Brazil. We discuss the theoretical and practical implications of our study and close with some suggestions for future research.